1997
DOI: 10.1021/jf970465h
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Oxidation of Methyl Linoleate Encapsulated with Gum Arabic by Hot-Air-Drying and Freeze-Drying

Abstract: Methyl linoleate was encapsulated with gum arabic by two drying methods, hot-air-drying and freezedrying. The oxidation of methyl linoleate encapsulated by both methods depended on the relative humidity during storage. Methyl linoleate encapsulated by freeze-drying was more slowly oxidized than that encapsulated by hot-air-drying at any relative humidity. The initial fraction of nonencapsulated lipid in the hot-air-dried microcapsule was about 1%, and the fraction increased quickly in the early stage of storag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
45
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2
2

Relationship

5
4

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 12 publications
3
45
0
Order By: Relevance
“…Spray-drying is the most popular technique for preparing microcapsules 4) . Factors affecting the oxidative stability of the encapsulated lipid, such as the type of polyunsaturated fatty acid, kind of wall material, and weight ratio of the lipid to wall material, have been examined [5][6][7][8][9][10] . We reported that the oxidation proceeded more slowly for the linoleic acid encapsulated with maltodextrin in smaller oildroplets 7,8) .…”
Section: Introductionmentioning
confidence: 99%
“…Spray-drying is the most popular technique for preparing microcapsules 4) . Factors affecting the oxidative stability of the encapsulated lipid, such as the type of polyunsaturated fatty acid, kind of wall material, and weight ratio of the lipid to wall material, have been examined [5][6][7][8][9][10] . We reported that the oxidation proceeded more slowly for the linoleic acid encapsulated with maltodextrin in smaller oildroplets 7,8) .…”
Section: Introductionmentioning
confidence: 99%
“…The encapsulation of PUFA into a powdery matrix of a wall material is achieved by two operations: one is an emulsification of the PUFA with a dense solution of the wall material, and the other is a rapid dehydration of the emulsion. The encapsulated PUFA is oxidized much more slowly than the bulk one (Maloney et al, 1966;Imagi et al, 1990;Minemoto et al, 1997;Minemoto et al, 2002). The oxidation process of PUFA encapsulated by hot-air-drying using a single-droplet method possessed two characteristic features.…”
mentioning
confidence: 99%
“…Soluble soybean polysaccharide, which is a water-soluble polysaccharide extracted and reˆned from soybean and includes about 9z proteinous or peptidyl components, possesses both these characteristics 6) and seems to be a promising wall material for lipid microencapsulation, similar to gum arabic. 7) The oxidation process of an encapsulated lipid undergoes two stages: one is a rapid decrease in the fraction of unoxidized substrate in the early stage of storage, and the other is leveling oŠ of the fraction with prolonged storage. 5,7) The kind of wall material is one of factors aŠecting this process.…”
mentioning
confidence: 99%
“…7) The oxidation process of an encapsulated lipid undergoes two stages: one is a rapid decrease in the fraction of unoxidized substrate in the early stage of storage, and the other is leveling oŠ of the fraction with prolonged storage. 5,7) The kind of wall material is one of factors aŠecting this process. 3,5) A polysaccharide was used in this study as the wall material for the microencapsulation of linoleic acid by spray-drying, and the oxidative stability of the encapsulated linoleic acid was examined to assess the characteristics of the polysaccharide as a wall material.…”
mentioning
confidence: 99%